Identification of novel therapeutic targets for histone 3 mutated children's brain tumour, using unique tumour cell surface proteomic signatures. (15th October 2021) - Snary, Anya; Grundy, Richard; Layfield, Rob; Rahman, Ruman; Haque, Farhana
Abstract: Aims: Improvements in the treatments for childhood and adolescent brain tumours, High-Grade Glioma (pHGG) and Diffuse Intrinsic Pontine Glioblastoma (DIPG), have not advanced much and they continue to carry a very poor prognosis. These brain tumours are now defined by mutations affecting histone 3 proteins, indeed 80% of DIPGs harbour histone H3.1 and H3.3 K27M somatic mutations whilst 30% of pHGGs exhibit H3.3 G34R or G34V mutations. We hypothesized that the histone 3 mutant tumours will have distinct mutation specific surfactome (cell membrane proteins) signature. Method: We therefore analysed the cell surface proteomics of pHGG and DIPG, in order to identify novel targets for therapy. We have at first isolated the cell membrane fractions from a range of patient cells carrying different histone 3 mutations (G34R, G34V), relative to wild type histone 3. A comparative quantitative mass-spectrometry analyses of these cell surface membrane fractions is then performed. Results: The results obtained to date demonstrated unique differential cell membrane expression patterns which correlated to specific mutation type. For example, increased expression of Ras-related proteins Rab-3, Rab-3D is detected only in histone H3.3-G34R mutated cell line in comparison. Conclusion: Identification and analyses of these unique cell membrane proteins' association with specific in H3.3 mutation in pHGG, will help to identify precise mutation specific therapeutic targets, benefiting the patients to receive therapy based on tumour's molecular signature.